2016
DOI: 10.2147/mder.s77993
|View full text |Cite
|
Sign up to set email alerts
|

Lasers in tattoo and pigmentation control: role of the PicoSure® laser system

Abstract: Background and objectivesThe use of picosecond lasers to remove tattoos has greatly improved due to the long-standing outcomes of nanosecond lasers, both clinically and histologically. The first aesthetic picosecond laser available for this use was the PicoSure® laser system (755/532 nm). Now that a vast amount of research on its use has been conducted, we performed a comprehensive review of the literature to validate the continued application of the PicoSure® laser system for tattoo removal.Study design and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The "bubble-like" cavitation phenomenon appeared as a circular array of dark fine granules that seemed to surround the lysosomal lobes. In physics, this phenomenon has been reported to be caused by photoacoustic or photomechanical effects [ 14 , 15 ]. This distinguishing ultrastructural feature suggests that the photoacoustic effect is another main mechanism of action in picosecond laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "bubble-like" cavitation phenomenon appeared as a circular array of dark fine granules that seemed to surround the lysosomal lobes. In physics, this phenomenon has been reported to be caused by photoacoustic or photomechanical effects [ 14 , 15 ]. This distinguishing ultrastructural feature suggests that the photoacoustic effect is another main mechanism of action in picosecond laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to remove specific colors has been reported to be mainly due to the specific wavelength rather than the pulse duration [ 15 ]. However, we found that the 1064 nm picosecond laser exhibited overall moderate response to other colors as well as black.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers operating in the visible spectral region particularly 532 nm has been widely used in medical technology such as skin rejuvenation, platelet aggregation, laryngeal lesions, acne treatment, tattoo and pigmentation control, prostate surgery, cardiovascular surgery, vascular lesions, glaucoma treatment, tissue remodeling, reduction in facial wrinkles etc. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Nevertheless, biological effects of laser signify it as a competent tool as well as a potentially hazardous device presenting with unforeseen occupational risks to operators and ancillary personnel [21].…”
Section: Introductionmentioning
confidence: 99%